The Benefits of Fighting the Enemies of Islam In the Light of Surat At-Tawbah: A Case Study of The Battle of Al-ʼaqṣā Flood - Bey Zekkoub, Abdelali (LECTURES: Journal of Islamic and Education Studies, 2024)
Islam has made it obligatory to fight aggressors according to the Qur'ān and Sunnah, as a means of preserving religion from extinction, protecting the soul from destruction, safeguarding the mind from corruption, defending honor from violation, preventing financial loss, and securing land from occupation. However, when Muslim leaders neglected this duty, it led to the domination of enemies over Muslim countries and the imposition of a secular lifestyle upon them. Therefore, it is crucial to dedicate a study to this topic in order to strengthen Muslims, encourage them to confront their enemies, and contribute to the victory of Islam and Muslims. This research seeks to extract the benefits of fighting enemies through verses 14 and 15 of Surah At-Tawbah and to examine their impact on the Battle of Al-ʼaqsā Flood (2023). The study employs inductive, deductive, and descriptive-analytical approaches. The study found the following results: (1) Fighting the enemies of Islam means deterring any attempt and thwarting any conspiracy that aims to destabilize the security of any Muslim country and threatens the lives of its residents, all for the sake of Allah, the Almighty; (2) Extracting six Quranic benefits of fighting enemies, including: killing the enemies, humiliating them, granting victory to the Muslims, experiencing the joy of victory, alleviating the Muslims' anger towards those who wronged them, and strengthening the Muslims' faith while correcting the beliefs of the disbelievers in the face of this victory; (3) All of these benefits were clearly evident during the Battle of Al-ʼaqsā Flood; (4) Extracting thirty benefits from the outcomes of the Battle of Al-ʼaqsā Flood. Moreover, these identified benefits and their application to the Battle of the Flood serve as a powerful motivation for Muslims to have strong faith in Allah, the Almighty, and to trust in His promise of victory over the enemies. They also provide a fundamental foundation for inspiring and encouraging Muslims to fight the aggressors until victory or martyrdom.